2003
DOI: 10.1046/j.1365-2869.2003.00356.x
|View full text |Cite
|
Sign up to set email alerts
|

Insomnia related to postmenopausal syndrome and hormone replacement therapy: sleep laboratory studies on baseline differences between patients and controls and double‐blind, placebo‐controlled investigations on the effects of a novel estrogen–progestogen combination (Climodien®, Lafamme®) versus estrogen alone

Abstract: Insomnia related to postmenopausal syndrome and hormone replacement therapy: sleep laboratory studies on baseline differences between patients and controls and double-blind, placebo-controlled investigations on the effects of a novel estrogen-progestogen combination (Climodien Ò , Lafamme Ò ) versus estrogen alone

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
45
0
2

Year Published

2004
2004
2017
2017

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 74 publications
(48 citation statements)
references
References 66 publications
1
45
0
2
Order By: Relevance
“…A confirmatory part, in which techniques for coping with multiplicity are applied for a predefined subarea of variable/region combinations which appear most important with respect to the goals of the study (adjusted alpha probability = 5%). The primary target variable in the present study in postmenopausal insomnia patients was 'wakefulness during the total sleep period', as determined by polysomnographic recordings evaluated according to Rechtschaffen and Kales [60], and has been reported elsewhere [61]. The ERP variables were included in the second, descriptive part.…”
Section: Statistical Analysesmentioning
confidence: 99%
“…A confirmatory part, in which techniques for coping with multiplicity are applied for a predefined subarea of variable/region combinations which appear most important with respect to the goals of the study (adjusted alpha probability = 5%). The primary target variable in the present study in postmenopausal insomnia patients was 'wakefulness during the total sleep period', as determined by polysomnographic recordings evaluated according to Rechtschaffen and Kales [60], and has been reported elsewhere [61]. The ERP variables were included in the second, descriptive part.…”
Section: Statistical Analysesmentioning
confidence: 99%
“…studies conducted by saletu-zyhlarz et al revealed that the total amount of sleep and its efficacy increased after applying climodien and Estradiol, but they remained unchanged with the placebo. Unfortunately, the described changes did not reach a statistically significant level [31].…”
Section: Discussionmentioning
confidence: 88%
“…Several previous sleep EEG studies resulted in confl icting results probably refl ecting differences in studied subjects and used hormonal treatments [e.g. [41][42][43] . Several possible direct or indirect mechanisms of action of estrogens or progestins have been discussed in this context [ for reviews, see 11,44] .…”
Section: Discussionmentioning
confidence: 99%